ChemInform Abstract: Solution‐Phase Microwave Assisted Parallel Synthesis of N, N′‐Disubstituted Thioureas Derived from Benzoic Acid: Biological Evaluation and Molecular Docking Studies. Issue 19 (13th May 2014) - Rauf, Muhammad Khawar; Talib, Ammara; Badshah, Amin; Zaib, Sumera; Shoaib, Khurram; Shahid, Mohammad; Floerke, Ulrich; Imtiaz‐ud‐Din, Ulrich; Iqbal, Jamshed
Abstract 26 Title compounds are prepared and preliminarily screened for their in vitro urease inhibition and antifungal activity.